Analisis Tingkat Kesenangan Siswa Dalam Mengikuti Pembelajaran Penjas Selama Masa Pandemi Covid-19 - Galang delvis sibly, - (2022)
Penelitian ini bertujuan untuk menganalisis tingkat kesenangan siswa dalam mengikuti pembelajaran penjas selama masa pandemi Covid-19. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Populasi dalam penelitian ini adalah siswa kelas XI SMA Negeri 1 Jampangkulon. Sampel penelitian sebanyak 105 orang siswa. Penelitian ini menggunakan insturmen kuisioner penelitian skala kesenangan aktivitas jasmani atau instrument Physical Activity Enjoyment Scale (PACES) yang diadopsi dari Kendzierski, D. and DeCarlo. Teknik analisis data yang digunakan pada penelitian adalah analisis statistik deskripsi persentase. Hasil analisis dan pengolahan data memperoleh hasil 85,743. Kesimpulan tingkat kesenangan siswa dalam mengikuti pembelajaran penjas selama masa pandemi Covid-19 berada pada kategori sedang yang menandakan bahwa tingkat kesenangan siswa dalam pembelajaran penjas selama masa pandemi Covid-19 adalah biasa saja. Galang Delvis Sibly Thesis: Analysis of Students' Enjoyment Levels in Participating in Physical Education Learning During the Covid-19 Pandemic. This thesis is supervised by Dr. Yusuf Hidayat, M.Sc. and H. Carsiwan, M.P.d. Health and Recreation Physical Education Study Program, University of Education Indonesia, 2022. This study aims to analyze the level of enjoyment of students in participating in physical education learning during the Covid-19 pandemic. The method used in this research is descriptive quantitative. The population in this study were students of class XI SMA Negeri 1 Jampangkulon. The research sample was 105 students. This study used a questionnaire instrument to study the Physical Activity Enjoyment Scale (PACES) which was adopted from Kendzierski, D. and DeCarlo. The data analysis technique used in this research is statistical analysis of percentage description. The results of data analysis and processing obtained 85,743 results. In conclusion, the level of enjoyment of students in participating in physical education learning during the Covid-19 pandemic is in the moderate category which indicates that the level of enjoyment of students in participating in physical education learning during the Covid-19 pandemic is normal.